Saving Germany : North American Protestants and Christian mission to West Germany, 1945 1974 - Enns, James, 1959- (Montreal ; Kingston ; London ; Chicago : McGill-Queen's University Press, 2017)
"This book explores the efforts of North American Protestant missionaries to rebuild and evangelize postwar Germany. The combination of Germany's failed experiment with National Socialism, its devastation from Allied bombs, and its early postwar reception of displaced people and refugees from Eastern Europe transformed the image of Germany in the minds of North American Protestants. In the US, effective lobbying by the Federal Council of Churches helped soften the administration's initial imposition of a harsh peace on Germany thus allowing voluntary aid from North American churches to flow into the country. This set the stage for a concerted missionary response from mission agencies which lasted through the Cold War period. Enns tracks this transnational Christian engagement in Germany from 1945 until the mid-1970s. He argues that North American Protestants (Canadians and Americans) engaged in two different kinds of mission work, and can be organized into three groups. Those from mainline Protestant denominations comfortable within the emerging ecumenical movement tended to see Nazism as an aberration in German history and understood their chief aim as the reconstruction of Germany and its churches. This included not only physical reconstruction but also the international rehabilitation of German Protestant leaders and the promotion of democracy within church institutions. Those from conservative evangelical traditions tended to see Germany as a post-Christian nation in need of reconversion and understood their chief aim as evangelization; this included the organization of mass evangelistic revivals, the production of Christian print material and radio programming, and the training of Christian preachers, teachers, and leaders. A third group--denominational missionaries from Mennonite, Baptist, Salvation Army, and Quaker traditions--engaged in both relief and evangelistic work. Enn selects a small number of mission organizations from each of these three groups to serve as case studies, which form the basis of the main chapters. The study pursues several ideas and lines of argument: the shift in North American Protestant missionary self-understanding from evangelization to assistance towards self-help, as well as the growing rift within the missions; the important ideological support North American missionaries gave to US foreign policy goals of the promotion of democracy and opposition to communism; the impact of North American missionary work on Protestant churches in West Germany; developments in 'world Christianity,' as Europe became identified as a post-Christian mission field; the significance of religious actors and the religious sphere in the cultural history of 'Americanization'".--
Includes bibliographical references and index.
Keywords: Protestant churches -- Missions -- Germany (West) -- History -- 20th century; Protestants -- Germany (West) -- History -- 20th century; Evangelicalism -- Germany (West) -- History -- 20th century; Missions, Canadian -- Germany (West) -- History -- 20th century; Missions, American -- Germany (West) -- History -- 20th century; Evangelicalism; Missions, American; Missions, Canadian; Protestant churches -- Missions; Protestants; Germany (West); HISTORY / Europe / General; 1900-1999; History; Electronic books